2007
DOI: 10.1002/jbt.20176
|View full text |Cite
|
Sign up to set email alerts
|

Functional activity of the mouse flavin‐containing monooxygenase forms 1, 3, and 5

Abstract: Three functional mouse flavin-containing monooxygenases (mFMOs) (i.e., mFMO1, mFMO3, and mFMO5) have been reported to be the major FMOs present in mouse liver. To examine the biochemical features of these enzymes, recombinant enzymes were expressed as maltose-binding protein fusion proteins (i.e., MBP-mFMO1, MBP-mFMO3, and MBP-mFMO5) in Escherichia coli and isolated and purified with affinity chromatography. The substrate specificity of these three mouse hepatic FMO enzymes were examined using a variety of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Consistent with increased Fmo3 mRNA expression in Nrf2 KO mice administered APAP (400 mg/kg) at 72 h, Fmo3 protein levels are also significantly higher (5.1±1.3-fold) compared to vehicle control group. Measuring FMO catalytic activity using MMI can also quantitate Fmo3 protein induction(Zhang et al, 2007). FMO specific activity increased significantly in Nrf2 KO livers (48±6±M/min/mg) at 72 h after APAP compared to vehicle controls of either genotype (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with increased Fmo3 mRNA expression in Nrf2 KO mice administered APAP (400 mg/kg) at 72 h, Fmo3 protein levels are also significantly higher (5.1±1.3-fold) compared to vehicle control group. Measuring FMO catalytic activity using MMI can also quantitate Fmo3 protein induction(Zhang et al, 2007). FMO specific activity increased significantly in Nrf2 KO livers (48±6±M/min/mg) at 72 h after APAP compared to vehicle controls of either genotype (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of probe substrates, the potential physiological function and substrate specificity of FMO5 remain poorly understood. The low catalytic efficiency of FMO5 toward common FMO substrates was speculated to be due to its lack of the reactive C(4␣)-hydroperoxyflavin (Ziegler 2002;Zhang et al, 2007). In this study, we report a unique probe reaction: a Baeyer-Villiger oxidation that is specifically catalyzed by FMO5.…”
Section: Baeyer-villiger Oxidation By Fmo5mentioning
confidence: 88%
“…When its activity was assessed using traditional FMO substrates such as methimazole, ranitidine, and cimetidine, FMO5 showed very poor affinity and narrow selectivity (Overby et al, 1997). In addition, FMO5 also demonstrated atypical characteristics in terms of thermal stability and pH dependence in comparison with other FMO isoforms (Zhang et al, 2007). S-Oxidation of S-methylesonarimod was known to be mediated by FMO1, 3, and 5, but this reaction was not specific to FMO5 (Ohmi et al, 2003).…”
Section: Baeyer-villiger Oxidation By Fmo5mentioning
confidence: 99%
“…Although highly expression of FMO5 is found in the liver of mice (14) and humans (15), but very little is known about the function of this protein. The knowledge on FMO5 substrates is limited (16)(17)(18): Known catalysis of FMO5 are the N-oxygenation of short-chain aliphatic primary amines such as N-octylamine (19) and the S-oxygenation of S-methyl-esonarimod, an active metabolite of the antirheumatic esonarimod (17,20). Sandra found that interindividual variation in FMO5 expression (8,16,21,22) might make contribution to diversity in fat deposits and plasma cholesterol, and some therapeutic agents induced FMO5 expression may have an adverse effect on the patient's metabolic health (23,24).…”
Section: Discussionmentioning
confidence: 99%